Evaluation of the Diagnosis and Treatment of Gallstone Pancreatitis - Ayudyasari, Wulan; Philippi, Bennardus; Poniman, Taslim; Saunar, Rofi Yuldi (Ikatan Ahli Bedah Indonesia, 2017)
Introduction. Acute pancreatitis is a major health problem due to the serious complication and mortality. Annual incidence of acute pancreatitis vary from under 10 to 40 per 100.000 person per year. Gallstone and biliary sludge contributes about 30-65% of the cause of acute pancreatitis and usually diagnosed as biliary or gallstone pancreatitis. There is still no data concerning the prevalence, diagnosis and management of gallstone pancreatitis in Indonesia. Methods. The objective of this study is to know the prevalence and characteristic of diagnosis and management of gallstone pancreatitis in some hospitals in Jakarta. This is a descriptive cross sectional study using the data from medical record of acute pancreatitis and gallstone pancreatitis patients in Cipto Mangunkusumo, Fatmawati, and St Carolus Hospital in 2008-2012. Results. There were 154 acute pancreatitis patients with only 22 (14,2%) patients diagnosed as having gallstone pancreatitis and 24 (15,5%) patients that met the criteria of gallstone pancreatitis but were not diagnosed as having one. On average, gallstone pancreatitis were diagnosed on the fifth day of hospitalization. Among 46 gallstone pancreatitis patients, only 6 (13%) patients had severity assessment. The most frequent examination used to explore the causes was abdominal ultrasound, performed in 37 (80,4%) patients.One (2,2%) patient had biliary sepsis and underwent internal drainage on day 15th. Only 10 (21,7%) patients underwent cholecystectomy. Three (8,3%) patients died, all before having cholecystectomy. Two (5,6%) patients that had not undergone cholecystectomy got readmitted to the hospital due to recurrent acute pancreatitis and pancreatic pseudocyst. Conclusion. From this study we can conclude that the diagnosis and management of gallstone pancreatitis still remain a challenge in Jakarta.